Hiatal Hernia Surgery An Evidence Based Approach (Springer International Publishing, 2018)
This book aims to address the recent advances and controversies on the subject of hiatus hernia and antireflux surgery. The field of antireflux surgery is undergoing a lot of changes, and traditional concepts are being challenged. The readers are provided with an evidence based approach to assist surgeons' decisions in developing a preoperative investigative algorithm prior to offering a surgical solution for either primary or recurrent hiatal hernia surgery based on supporting evidence. The chapters will further investigate the latest trends in minimally invasive hiatal hernia and antireflux surgery, both for primary and recurrent hernias.